2005
DOI: 10.1177/0891241604274263
|View full text |Cite
|
Sign up to set email alerts
|

Polyamorous Women, Sexual Subjectivity and Power

Abstract: This article explores polyamorous women’s potential to enlarge the concept of sexual subjectivity through their engagement in nontraditional relationships and their attempts to reject sexual objectification. Polyamorous people openly engage in romantic, sexual, and/or affective relationships with multiple people simultaneously. Polyamory differs from swinging with its emphasis on long-term, emotionally intimate relationships and from adultery with its focus on honesty and (ideally) full disclosure of the netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 15 publications
6
82
0
3
Order By: Relevance
“…There are many types of multipartner sexualities that are conflated orco-implicateddespitehavingaverydifferentsetofbehaviorsand livedexperiences(e.g., Barker,2005;Ritchie&Barker,2006;Rust, 2001Rust, , 2003Sheff, 2005). This is paralleled by the many identities used in polyamory and multiple partner discourse (Ritchie & Barker, 2006).…”
Section: Heterosexual and Mostly Heterosexualmentioning
confidence: 89%
See 2 more Smart Citations
“…There are many types of multipartner sexualities that are conflated orco-implicateddespitehavingaverydifferentsetofbehaviorsand livedexperiences(e.g., Barker,2005;Ritchie&Barker,2006;Rust, 2001Rust, , 2003Sheff, 2005). This is paralleled by the many identities used in polyamory and multiple partner discourse (Ritchie & Barker, 2006).…”
Section: Heterosexual and Mostly Heterosexualmentioning
confidence: 89%
“…For example, polyamory, slut, 14 and asexuality are identities that I argue are organized in part around partner number. Empirical evidence also provides important support for including partner number sexuality (Barker & Langdridge, 2010;Bogaert, 2004;Brotto et al, 2010;Carrigan, 2011;Klesse, 2006;Scherrer, 2008;Sheff, 2005). And, logical considerationsalmost necessitateits inclusionbecause a person must be interested in at least one sexual partner before their gender/sex sexuality could even be a consideration.…”
Section: Parameter 2: Partner Number Sexualitymentioning
confidence: 95%
See 1 more Smart Citation
“…Jackson and Scott (2004) found that women would be less likely to become dependent, isolated, and detached from their communities. Polyamorous women were able to expand their family, cultural, gender, and sexual roles as they felt empowered by their greater freedom to make their own sexual choices, create new roles for themselves, and express themselves sexually (Sheff, 2005). Furthermore, nonmonogamies can be potentially liberating, cooperative and empowering alternatives to the ownership, possession, and even violence located within traditional monogamy for women (Mint, 2010).…”
Section: Benefits To Polyamorymentioning
confidence: 95%
“…One nonmonogamous family structure that may appear more preferable is polyamorous relationships, sometimes referred to as "the postmodern polygamy" (Gher 2008, 572;Sheff 2005). "Polyamory" is a relationship of multiple men and women.…”
mentioning
confidence: 99%